PELATIHAN DASAR-DASAR AKUNTANSI DI PANTI ASUHAN ASIH LESTARI - Dermawan, Elizabeth Sugiarto; Suzanna; Wibaewa, Axel (Jurnal Serina Abdimas, 2024)
The background is because many people say that accounting will be replaced by computers, but the basic understanding still needs to be studied.Likewise, mathematics cannot be replaced by a calculator. In this era of technological development, accounting knowledge still needs to be understood in order to be able to prepare financial reports that are presented correctly.This community service was carried out on the basis of invitation no.002/YPA.AL/SK/I/2024 from the management of the Asih Lestari (AL) Orphanage which required basic accounting training to equip the students in the orphanage. An understanding of accounting is needed to equip orphanage students so that after high school they will try to be independent and have no difficulty in making financial reports for their business. This PKM is expected to provide an understanding of the basics of accounting which can be useful for supporting learning at school and enriching understanding in preparing for independent business in the future. Community service implementation was carried out on Monday, March 11 2024, pk. 09.00-13.00, with tutorials, exercises and evaluation through quizzes and questionnaires. This community service has been carried out so well that most of the orphanage students intend to deepen the basics of accounting. The mandatory output of Community Service is presented in SERINA VIII 2024, while an additional output is created as a module for Intellectual Property Rights (IPR). ABSTRAK Dilatar belakangi karena banyak pihak mengatakan bahwa akuntansi akan digantikan dengan komputer, namun dasar pemahamannya tetap perlu dipelajari. Sama halnya dengan matematika yang tidak dapat digantikan oleh kalkulator. Dalam era perkembangan teknologi, ilmu akuntansi tetap perlu dipahami agar dapat membuat laporan keuangan yang disajikan dengan tepat. Pengabdian Kepada Masyarakat ini dilakukan atas dasar undangan no.002/YPA.AL/SK/I/2024 dari pengelola Panti Asuhan Asih Lestari (AL) yang membutuhkan pelatihan Dasar-Dasar Akuntansi untuk membekali siswa-siswi yang berada dalam panti tersebut. Pemahaman akuntansi diperlukan untuk membekali siswa-siswi panti agar selepas SMA dimana mereka akan berusaha mandiri dan tidak kesulitan dalam membuat laporan keuangan usahanya. PKM ini diharapkan membekali pemahaman dasar-dasar akuntansi yang dapat bermanfaat untuk menunjang pembelajaran di sekolah maupun memperkaya pemahaman dalam mempersiapkan usaha mandiri di masa depan. Pengabdian Kepada Masyarakat ini telah dilaksanakan pada hari Senin tanggal 11 Maret 2024 pk. 09.00-13.00, dengan cara tutorial, latihan, dan evaluasi melalui kuis serta angket. PKM ini telah terlaksana dengan baik hingga siswa-siswi panti asuhan ini sebagian besar berniat untuk memperdalam dasar-dasar akuntansi. Luaran wajib Penabdian Kepada Masyarakat ini disajikan dalam SERINA VIII 2024, sedangkan luaran tambahan dibuatkan modul untuk Hak Kekayaan Intelektual (HKI).